The white man's burden : why the West's efforts to aid the rest have done so much ill and so little good - Easterly, William, 1957- (New York : Penguin Press, 2006)
"An attack on the tragic waste, futility, and hubris of the West's efforts to date to improve the lot of the so-called developing world, with constructive suggestions on how to move forward. Economist Easterly discusses the twin tragedies of global poverty: the first, that so many are seemingly fated to live miserable lives and die early deaths; the second, that after fifty years and more than $2.3 trillion in aid, we have shockingly little to show for it. We preach a gospel of freedom and individual accountability, yet we intrude in the inner workings of other countries through bloated aid bureaucracies--and most of the places in which we've meddled are in fact no better off or are even worse off than they were before. Could it be that we don't know as much as we think we do?"--Publisher description.
Planners versus searchers -- Why planners cannot bring prosperity -- The legend of the big push -- You can't plan a market -- Planners and gangsters -- Acting out the burden -- The rich have markets, the poor have bureaucrats -- Bailing out the poor -- The healers : triumph and tragedy -- The white man's army -- From colonialism to postmodern imperialism -- Invading the poor -- The future -- Homegrown development -- The future of Western assistance.
Includes bibliographical references and index.
Keywords: Economic assistance -- Developing countries; Economic development -- Developing countries; Poverty -- Prevention